Extinctive prescription on the limitation of actions : reports of the XIVth Congress, International Academy of Comparative Law, Athens (Vouliagmeni), Greece 31 July-7 August 1994 /: reports of the XIVth Congress, International Academy of Comparative Law, Athens (Vouliagmeni), Greece 31 July-7 August 1994. (1995) - Unknown
No abstract available